Analysis of Effective Marketing Strategies for Environmentally Friendly Products - Tengku Kespandiar; Luh Komang Candra Dewi; Agus Nurofik; Heny Hidayati; Asnawati Asnawati (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
Companies that develop environmentally friendly products are closely connected to product development theory, which positions product development as a growth strategy through modified or new offerings for a defined target market. Product development applies to physical products and focuses on transforming initial ideas into more effective and competitive products. In parallel, marketing strategy functions as a planned effort to implement and control activities that influence market exchanges in order to achieve organizational objectives. A key stage in marketing strategy design is the marketing mix, which includes product, price, place, and promotion. This study aims to understand and analyze effective marketing strategies for environmentally friendly products. Using a narrative approach, the study synthesizes insights from relevant secondary sources to explain the relationship between green products and strategic marketing practices. The results indicate that effective marketing strategies for environmentally friendly products include highlighting sustainability values in branding, educating consumers about environmental and functional benefits, leveraging social media for green campaigns, collaborating with environmental influencers, and strengthening credibility through green certification and clear eco-labeling. These strategies help increase consumer trust and improve market acceptance of environmentally friendly products.